La crianza como un proceso de humanización en la cultura afro descendiente (2015)
This article builds a description of the different rearing practices implemented in communities of African descent to formation their children. It begins with the analysis of the meaning of the word “afro- descendant” and a brief journey through its history marked by pain and domination. It does so in order to understand the concepts related to parenting, understood as a process, and to therefore, elucidate the importance of culture and the influence it has on the care and formation human beings and the word views they may have. The ultimate goal is to obtain a detailed description of some practices carried out by communities of African descent to ensure the existence of their culture.